Morphological and metabolic adjustments in the small intestine to energy demands of growth, storage, and fasting in the first annual cycle of a hibernating lizard (Tupinambis merianae) - Nascimento, Lucas Francisco R. do; Silveira, Lilian Cristina da; Nisembaum, Laura Gabriela; Colquhoun, Alison; Abe, Agusto S. [UNESP]; Mandarim-de-Lacerda, Carlos Alberto; Souza, Silvia Cristina R. de (Elsevier B.V., 2016)
Seasonal plasticity in the small intestine of neonatal tegu lizards was investigated using morphometry and analysis of enzymes involved in supplying energy to the intestinal tissue. In the autumn, the intestinal mass (Mi) was 1.0% of body mass and the scaling exponent b = 0.92 indicated that Mi was larger in smaller neonates. During arousal from dormancy Mi was 23% smaller; later in spring, Mi increased 60% in relation to the autumn and the exponent b = 0.14 indicated that the recovery was disproportionate in smaller tegus. During the autumn, the intestinal villi were greatly elongated; by midwinter, the Hv, SvEp, and VvEp were smaller than during the autumn (59%, 54%, 29%) and were restored to autumn levels during spring. In the active tegus, the maximum activity (Vmax) of enzymes indicated that the enterocytes can obtain energy from different sources, and possess gluconeogenic capacity. During winter, the Vmax of CS, HOAD, GDH, PEPCK was 40-50% lower in relation to the autumn and spring, while the Vmax of HK, PK, LDH, AST was unchanged. The hypoglycemia and the mucosal atrophy/ischemia during winter would prevent the enterocytes from using glucose, whereas they could slowly oxidize fatty acids released from body stores and amino acids from the tissue proteolysis to satisfy their needs of energy. Contrastingly, starvation during spring caused severe mass loss (50%); the tissue protein and the VvEp and VvLP did not change while the thickness of the muscular layer increased 51%, which suggested different effects along the length of the organ. In addition, the Vmax of the glycolytic enzymes was lower, indicating that a regulatory mechanism would spare blood glucose for vital organs during unanticipated food restriction. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Seasonal dormancy; Hibernation; Hypometabolism; Fasting; Starvation; Intestine; Scaling; Metabolic enzymes; Tegu lizard; Tupinambis merianae